2019
DOI: 10.2174/1871530319666190226165910
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Platelet Lysate in Differentiation of Wharton’s Jelly Derived Mesenchymal Stem Cells

Abstract: Background: Mesenchymal stem cells (MSCs) are highly preferred in clinical therapy for repair and regeneration of diseased tissues for their multipotent properties. Conventionally, MSCs have been cultured in media supplemented with animal derived serum, however, it is ideal to expand MSCs in media containing supplements of human origin for clinical therapy. Currently, a number of human derived products are being studied as an alternative to animal sources. Amongst these, platelet lysate (PL) has gained interes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
2
1
Order By: Relevance
“…Interestingly, hPL showed high expression of all tested markers (<90%). These results differ from other studies where no effect of the medium supplement was observed [ 44 , 45 , 46 ]. There was no statistical difference in mesenchymal stem cell markers (CD29, CD44, CD73, CD90) and stromal-associated markers (CD13 and CD166).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Interestingly, hPL showed high expression of all tested markers (<90%). These results differ from other studies where no effect of the medium supplement was observed [ 44 , 45 , 46 ]. There was no statistical difference in mesenchymal stem cell markers (CD29, CD44, CD73, CD90) and stromal-associated markers (CD13 and CD166).…”
Section: Discussioncontrasting
confidence: 99%
“…hPL-cultivated hNDP-SCs showed approximately two times shorter PDT (22.65 ± 0.10 h) compared with the FBS-cultivated group (44.69 ± 1.36 h), while the PDs per passage were the same (3.97 ± 0.35 vs. 3.98 ± 0.38). Our results are comparable with other studies [ 26 , 36 , 39 , 40 , 43 , 44 ]. At the end of cell growth, we observed the prolongation of population doubling time in the hPL-treated group.…”
Section: Discussionsupporting
confidence: 93%
“…It was observed in some studies that supplementation with HPLs versus FBS favors MSC differentiation into chondrocytes [ 126 , 128 , 130 , 169 ]. HPLs are also a suitable supplement to expand MSCs from other tissue sources such as Wharton jelly [ 126 , 170 ], umbilical cords [ 171 174 ], amniotic fluid [ 175 , 176 ], dental pulp [ 177 179 ], periodontal ligaments [ 180 ], and others [ 121 ]. HPLs are therefore emerging as a universal supplement for in vitro xeno-free expansion of MSCs [ 12 , 121 , 181 ] for clinical transplantation.…”
Section: Use Of Allogeneic Hpl For Cell Propagationmentioning
confidence: 99%
“…Media supplemented with FBS are widely used to provide a supportive environment for isolation and expansion of MSCs from various sources, despite notorious practical, clinical, and ethical concerns over FBS use, essentially due to the presence of undesirable toxins, pathogen agents and/or xenogeneic proteins ( Shahdadfar et al, 2005 ; van der Valk and Gstraunthaler, 2017 ). For this reason, in order to develop a clinically suitable and hazardous risk-free protocol for the isolation of Wharton’s jelly-derived MSCs (WJ-MSCs) from umbilical cords, many reports showed the potential of human platelet lysate (hPL) in enhancing MSCs recovery and propagation ( de Soure et al, 2017 ; Becherucci et al, 2018 ; Kandoi et al, 2018 ; Vennila et al, 2019 ; Liao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%